Deep urban groundwater vulnerability in India revealed through the use of emerging organic contaminants and residence time tracers. (September 2018) - Lapworth, D.J.; Das, P.; Shaw, A.; Mukherjee, A.; Civil, W.; Petersen, J.O.; Gooddy, D.C.; Wakefield, O.; Finlayson, A.; Krishan, G.; Sengupta, P.; MacDonald, A.M.
Abstract: Demand for groundwater in urban centres across Asia continues to rise with ever deeper wells being drilled to avoid shallow contamination. The vulnerability of deep alluvial aquifers to contaminant migration is assessed in the ancient city of Varanasi, India, using a novel combination of emerging organic contaminants (EOCs) and groundwater residence time tracers (CFC and SF6 ). Both shallow and intermediate depth private sources (<100 m) and deep (>100 m) municipal groundwater supplies were found to be contaminated with a range of EOCs including pharmaceuticals (e.g. sulfamethoxazole, 77% detection frequency, range <0.0001–0.034 μg L −1 ), perfluoroalkyl substances (e.g. PFOS, range <0.0001–0.033 μg L −1 ) as well as a number of pesticides (e.g. phenoxyacetic acid, range <0.02–0.21 μg L −1 ). The profile of EOCs found in groundwater mirror those found in surface waters, albeit at lower concentrations, and reflect common waste water sources with attenuation in the subsurface. Mean groundwater residence times were found to be comparable between some deep groundwater and shallow groundwater sources with residence times ranging from >70 to 30 years. Local variations in aquifer geology influence the extent of modern recharge at depth. Both tracers provide compelling evidence of significant inputs of younger groundwater to depth >100 m within the aquifer system. Graphical abstract: Image 1 Highlights: Indian drinking water sources from groundwater contaminated with EOCs. Deep groundwater vulnerable to modern recharge and EOC contamination. Anti-microbial compounds and other organic compounds frequently detected. Higher concentrations and numbers of EOCs found in surface waters.